THE IMPORTANCE OF SELF-FEEDING TRAINING AND DYSPHAGIA REGIMENS IN A RESIDENTIAL SOCIAL SERVICE USER WITH A COMBINED DISABILITY - Petra Křížkovská; Kateřina Kroupová (Listy klinicke logopedie)
The article presents partial successes within the framework of the intervention of a vision therapist/therapist for the visually impaired in one person and a clinical speech therapist in collaboration with an occupational therapist, for a client with a combined disability in the area of self-feeding and setting regimen measures to deal with dysphagia symptoms. In addition to the aspect of independent food intake, other specific areas are also emphasised in which the client's independence is supported, with the aim of achieving the highest possible level of activation. The aim of the article is to describe the process of training self-feeding, together with its problematic areas, including the process of setting regimen measures related to the development of spatial orientation so that they suit a particular client in the context of social services provided. The importance of the intervention described above is crucial in terms of supporting the self-sufficiency of a person with a disability, with reference to the goals of providing social services, as well as of monitoring the safety of the process of food and fluid intake.